Pulmonary Brucellosis: a shrewd imposter - Ramachandran Satheebai, Parvathy; Asokan, Anil Kumar; Somasekaran, Harikrishnan; Surendran, Aswini Kumar; Sreehari, Sreedhanya; Nair, Arya R.; Chittathu Parambil Gopalakrishnan, Gowtham Kishore; Eapen, Aby C. (International Journal of Research in Medical Sciences, 2025)
Brucellosis is a zoonotic bacterial infection with a broad clinical spectrum, often mimicking other infectious and non-infectious diseases. Due to its nonspecific presentation, delayed diagnosis is common, leading to potential complications. We report a case of young female presented with fever, associated with constitutional symptoms, cervical lymphadenopathy and lower respiratory tract infection features. Her Tuberculosis workup, tropical fever and other viral infection workup, lymphoma evaluation and vasculitis work up were negative. She had persistent symptoms and later Brucella serology sent as she came from area where Brucellosis is endemic. The report came as positive for Brucellosis. The patient managed in intensive care unit with respiratory support, antibiotic and other supportive care. Later she became symptomatically better and had radiological clearance.